1985
DOI: 10.1121/1.2022377
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of low-frequency tones and narrow bands of noise

Abstract: It is well known and universally accepted that people's ability to use ongoing interaural temporal disparities conveyed via pure tones is limited to frequencies below 1600 Hz. We wished to determine if this limitation is the result of the constant amplitude and periodic axis crossings which characterize pure tones. To this end, we employed an acoustic pointing task in which listeners varied the interaural intensitive difference of a 500-Hz narrow-band noise (the pointer) so that it matched the intracranial pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…The upper limits for binaural hearing based on IPD in young subjects was ϳ1300 Hz, consistent with results of several previous studies (Garner and Wertheimer, 1951;Zwislocki and Feldman, 1956;Schiano et al, 1986;Macpherson and Middlebrooks, 2002) At frequencies above 1500 Hz, the IPD in tones becomes ambiguous in humans because ITD (determined by the head size) becomes larger than one period of the sound. Thus, the frequency limit could be thought as a meaningful outcome of evolutional specialization in humans.…”
Section: Discussionsupporting
confidence: 77%
“…The upper limits for binaural hearing based on IPD in young subjects was ϳ1300 Hz, consistent with results of several previous studies (Garner and Wertheimer, 1951;Zwislocki and Feldman, 1956;Schiano et al, 1986;Macpherson and Middlebrooks, 2002) At frequencies above 1500 Hz, the IPD in tones becomes ambiguous in humans because ITD (determined by the head size) becomes larger than one period of the sound. Thus, the frequency limit could be thought as a meaningful outcome of evolutional specialization in humans.…”
Section: Discussionsupporting
confidence: 77%
“…We found that the shape of p (~,,,~fc~) plays a primary role in determining the lateral position of high-frequency tones in Schiano et al (1986). In the Domnitz and Colburn experiment, the lateral position of each liD-curve follows a sinusoidal trend over ITD, and the cue-reversal points migrate with liD.…”
Section: Discussionmentioning
confidence: 95%
“…Section 2.1 describes the major stages used by the model to produce an estimate of lateralization. In Section 2.2 we review the model's predictions for the lateralization of tones experiments performed by Domnitz and Colburn (1977), and by Schiano et al (1986) …”
Section: Chapter 2 Review Of Position-variable Modelmentioning
confidence: 99%
See 2 more Smart Citations